Investor's guide : when, why & where to invest - Ojiako, James O. (Ibadan : The Caxton Press (West Africa) Limited Ibadan, 1970)
Investor's Guide is written to help the would-be investor in investing directly in equities: to know exactly what he wants to achieve by investing whether he is after quick profit, or whether he is preparing for a long term growth or just looking for income or capital gain.
osa; 24/07/18
Loans
Keywords: Investments; Nigeria